(untitled) (Journal of Informatics and Mathematical Sciences, 2025)
A graph \(G\) with \(p\) number of vertices, \(q\) number of edges and \(b\) number of blocks, where \(p,q,b1\). The set of vertices, edges and blocks are denoted by \(V(G)={v_1,v_2,… ,v_p}\), \(E(G)={e_1,e_2,… ,e_q}\) and \(B(G)={b_1,b_2,… ,b_n}\), respectively. The graph \(G\) admits AUM block labeling if there exists a bijection \(f:V(G)→ z^+\) induced from \(f\) by \(f^*(uv)=f(u)*f(v)\) and \(f^**(B_j)=B(G)→ z^+\) then \(f^**(B_j)=^n_i=1f(v_ij)+^n_i=1f^*(e_ij)\) and \(f^**(B_i) eq f^**(B_j)\). In this paper, we prove that the super subdivision of coconut tree and double coconut tree graph admits AUM block labeling.